2021
DOI: 10.1007/s40801-021-00273-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of Fondaparinux vs Enoxaparin in a Population of Indian Patients with Symptomatic Deep Vein Thrombosis: A Retrospective Real-World Study

Abstract: Background Fondaparinux is the first approved anticoagulant drug among factor Xa inhibitors, with proven effectiveness and safety in preventing deep vein thrombosis. However, limited data are available supporting the benefit-risk profile of fondaparinux vs enoxaparin in a real-world group of Indian patients with deep vein thrombosis. Objective To compare the effectiveness and tolerability of fondaparinux vs enoxaparin in patients with symptomatic deep vein thrombosis in a long-term real-world setting. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Non-major bleeding events have been previously reported in 13.2% of critically ill patients who received UFH as prophylactic anticoagulation therapy [ 20 ]. A recent real-world study reported minor bleeding events in 9.3% of patients who received fondaparinux or enoxaparin as anticoagulation therapy for symptomatic VTE [ 21 ]. The rate of minor bleeding events observed in this study was higher than that observed in the previous study, which may be attributed to patients presenting with trauma and a difference in the definition of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Non-major bleeding events have been previously reported in 13.2% of critically ill patients who received UFH as prophylactic anticoagulation therapy [ 20 ]. A recent real-world study reported minor bleeding events in 9.3% of patients who received fondaparinux or enoxaparin as anticoagulation therapy for symptomatic VTE [ 21 ]. The rate of minor bleeding events observed in this study was higher than that observed in the previous study, which may be attributed to patients presenting with trauma and a difference in the definition of bleeding.…”
Section: Discussionmentioning
confidence: 99%